Essays in business cycles: housing market, adaptive learning, and credit market imperfections - Li, Jinke (2012)
In this thesis, we focus on the housing sector, which is important to the economy but is under-researched in business cycles analysis. We discuss several housing sector related issues in dynamics stochastic general equilibrium (DSGE) models.